Factors that influence job stress among employees at Telekom Malaysia Kota Bharu / Jurinawati Suwadi - Suwadi, Jurinawati (2011)
The study was conducted at Telekom Malaysia Kota Bharu. This research was targeted on employees who are working at the TM Kota Bharu. The objectives of this study are to identify the factors that influence job stress among employees at TM Kota Bharu and to determine the relationship between organizational factors, personality traits and culture with the job stress at the TM Kota Bharu. The theoretical framework for this study consists of dependent variable and independent variable. Dependent variable for this research is job stress and independent variables are the factors that influence job stress. Researcher had identified three independent variables such as organizational factors, personality traits and culture that influence job stress. Data were collected through questionnaire that consists five sections. For this research, the sample size will be 100 respondents. Out of 100, 60 questionnaires was return back. A convenient sampling technique was used as a procedure to determine the sample for this study and the result was analyzed by using SPSS. The findings of this study show that all dependent variables which are organizational factors, personality traits and culture have relationship with the job stress but two out of these three factors which are organizational factors and personality traits positively influence job stress among employees at TM Kota Bharu. The other one factor which is culture not influences job stress among employees at TM Kota Bharu. From the result obtained in this study, researcher comes out with several recommendations in order to provide the alternative in reducing job stress among employees at TM Kota Bharu